Assessment of Learning in Mathematics Education: A Neoliberal Root of Colonialism - Lamichhane, Basanta Raj (Mathematics Education Forum Chitwan, 2024)
Assessment of learning (AfL) has been taken as one of the significant tools for assessing the students' learning outcomes in the educational landscape of Nepal and possibly other countries as well. However, it generally segregates the learners into two mutually exclusive groups of success and failure rather than exploring teaching-learning status for the grand purpose of improving it. AfL isolates the assessment from the learning because it is executed at the end of the academic session by external authorities in the name of maintaining the reliability and validity of the test to ensure quality standards of education. Against these backdrops, this argumentative paper tries to uncover how AfL becomes a tool in the hands of colonial power centres and supports indoctrinating neocolonial agendas of open markets backed by economic rationality. I have realized that AfL not only focuses on competition and efficiency without considering the sociocultural, historical and economic backgrounds of the learners but also neglects other aspects of education—collaboration, interdependence, mutual respect and empathy. Likewise, it supports for instigating blaming culture and a winner-takes-all approach mentality in practitioners contribute to perpetuating and legitimizing social, economic and epistemic injustices. I have also found that most of these attributes are the product of the neoliberal economic policy of the state that does nothing but hand over everything to the open market. From this perspective, AfL has promoted the agenda of neoliberalism, which is backed by colonialism. The implication is that before assessing the learning outcomes of the learners, we must take into consideration the sociocultural, historical and economic backgrounds of the learners and their ways of seeing, knowing and valuing the outer world; otherwise, the assessment becomes meaningless.